Comparison of Periodontal Intraligamental Anesthesia Using Etidocaine HCL and Lidocaine HCL - Johnson, Georgia K. (1985)
A double-blind method was used to compare anesthesia duration following intraligamental administration of 1.5% etidocaine with 1:200,000 epinephrine and 2% lidocaine with 1:100,000 epinephrine. Durations of anesthesia in pulpal and soft tissues were monitored following periodontal ligament injections adjacent to the maxillary canines of 20 individuals. Complete pulpal anesthesia was attained in 35% of the teeth injected with etidocaine and in 55% of those receiving lidocaine. Soft tissue anesthesia was consistently achieved. Both pulpal and soft tissue anesthesia were of longer duration following the use of lidocaine solution. These findings suggest that anesthetic duration following periodontal ligament injections is more related to the concentration of vasoconstrictor than to the anesthetic solution employed.